2017
DOI: 10.1111/jai.13328
|View full text |Cite
|
Sign up to set email alerts
|

Length weight relationships of two small indigenous cyprinid fishes, Osteobrama cotio (Hamilton, 1822) and Salmophasia phulo (Hamilton, 1822) from Panchet Reservoir, Damodar River (tributary of River Ganga), India

Abstract: Summary Length–weight relationships were determined for two small indigenous cyprinid fishes: Osteobrama cotio (Hamilton, 1822) and Salmophasia phulo (Hamilton, 1822) collected from Panchet reservoir, Damodar River, India. About 143 specimens of Osteobrama cotio (5.2–10.4 cm TL) and 113 specimens of Salmophasia phulo (2.9–8.2 cm TL) were collected from November 2014 to June 2016 using gillnets of mesh size ranging from 25 to 120 mm (STR) and dragnets of mesh size 10–20 mm (STR). No previous information on LWRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…According to Jhingran (1972) and Jhingran and Verma (1973), the species was abundant during seventies in Ganga river system. Fish composition structure, length-weight relationships of selected species and diversity of planktivorous fish of Panchet Reservoir was reported by Sandhya et al (2017;. Most of the studies have been conducted in rivers and wetlands on abundance but there is no previous report on LWRs of this species from an Indian reservoir (Froese and Pauly, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to Jhingran (1972) and Jhingran and Verma (1973), the species was abundant during seventies in Ganga river system. Fish composition structure, length-weight relationships of selected species and diversity of planktivorous fish of Panchet Reservoir was reported by Sandhya et al (2017;. Most of the studies have been conducted in rivers and wetlands on abundance but there is no previous report on LWRs of this species from an Indian reservoir (Froese and Pauly, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies on the impact assessment of fingerling stocking is inadequate although it occupies a major share in total large reservoir area of India. Such information is almost nil for large Indian reservoirs though a few researchers have reported fish assemblage pattern, diversity, and some biological aspects of fishes from large reservoirs (Kumari et al, 2018Lianthuamluaia et al, 2019;Sandhya et al, 2017Sandhya et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Present study describes the length-weight relationships of 18 fish species from a tropical large reservoir, Panchet in India comprising commercially important species as well as some of the small indigenous fishes. Only a few fish faunal studies have been reported from this reservoir; mostly limited to catch, fish diversity and LWRs of very few species (Sarkar and Banerjee, 2010;Sandhya et al, 2016Sandhya et al, , 2017Sandhya et al, , 2019Suman et al, 2018). Information on the lengthweight relationship of Puntius terio, Pethia conchonius, Sperata seenghala, Ailia coila and Trichogaster chuna from Indian reservoirs is lacking.…”
Section: Introductionmentioning
confidence: 99%